INCREASING ENGLISH VOCABULARY OF GRADE VIII STUDENTS THROUGH WORD GAMES - Kandolia, Zefanya Clavinova; Said, Mawardin M; Lebagi, Desrin; Mukrim, Mukrim (Universitas Muhammadiyah Makassar, 2025)
This research aims to find out whether or not the use of Word Games can effectively increase English vocabulary of grade VIII students at SMP Negeri 10 Palu. This research applied a quasi-experimental design that involved two classes, the experimental class and the control class. The sample of this research was the grade VIII students at SMP Negeri 10 Palu; VIII A consisted of 25 students as an experimental class and VIII B consisted of 25 students as a control class were selected by using simple random sampling. The data were collected through pretest and posttest. The data were analyzed by using SPSS application version 29. The result of the mean score in the experimental class on pretest is 53.44 and the control class is 50.08. The mean score of the posttest in the experimental class is 90.04 and the control class is 61.12. Independent samples t test showed that the significance is 0.000 and the standard significance is 0.05 which means that the value of significance is lower than the standard significance (0,000<0,05). It can be concluded that the use of Word Games can increase English vocabulary of the grade VIII students.